Techniques to Improve Elementary School Students' Reading Literacy - Ni Kadek Yunda Pradnyani; Anak Agung Gede Agung; Maria Goreti Rini Kristiantari (Jurnal Pendidikan dan Pengajaran, 2022)
This research is motivated by the low ability of students in literacy. The study aims to analyze the effect of scanning on the computer-based national assessment of reading literacy competence in fifth-grade students. The type of research used was a quasi-experimental design with a non-equivalent pretest-posttest control group design. This research was conducted with a total population of 253 students. The data collection method in this study is the test method, the test used is in the form of an objective test, with the types of tests used being multiple choice, complex multiple-choice, and matching questions totaling 30 validated questions. The collected data was normalized using the gain score and then analyzed using the t-test inferential statistics. Based on the results of data analysis, tcount= 9,453 more than ttable = 2,002 at a significance level of 5% (α = 0.05) with dk = (6-1) = 5, so there is a significant difference between the reading literacy competencies of students who are taught using scanning with those taught using conventional learning. Thus it can be concluded that the scanning effect on the reading literacy competence of fifth-grade students.